Developing Website-based Learning Media to Improve Students’ 5Cs Skills - Ayu Fitrianingsih; Cahyo Hasanudin; Nofia Fitriyana; Abather Saadoon (STAI Hubbulwathan Duri, 2023)
The 5Cs skills are critical thinking and problem solving, creativity and innovation, communication, collaboration, and confidence. It becomes essential skills in the 21st century. This study aims to investigate the strategies in creating website-based learning media. It is Research and Development (RD) which implements ADDIE model. Research subjects are 64 students in sixth semester of English Education Department at a private university in Bojonegoro Regency. In analyzing stage, need analysis is conducted to determine students’ need of it. In designing stage, the blueprints are created in form of storyboards. In developing stage, it is submitted and consulted to 2 validators who are learning media experts in different universities. In implementing stage, it is implemented in TEYL class to investigate its impact on students. In evaluating stage, Results of development show that website-based learning media is able to improve students’ 5Cs skills. It can be concluded that website-based learning media is able to improve students’ 5Cs skills.